Structural model of employee behavior measurement - Krüger, Cristiane; Minello, Italo Fernando (Revista de Negócios, 2019)
The traditional methods of evaluating entrepreneurial behavior carry a degree of uncertainty and subjectivity with several uncontrollable independent variables. Faced with this fragility, the modeling of structural equations can be a tool that contributes to the understanding of this behavior. In order to contribute in this direction, this study aimed to develop a structural model for measuring entrepreneurial behavior based on behavioral characteristics and entrepreneurial intent. The research is applied, quantitative, descriptive and exploratory. In order to satisfy the problem raised, data collection instruments already validated were used. The sample consisted of 2,519 respondents. The internal consistency of the scales proved to be reliable for the measurement and evaluation of the constructs. In the descriptive analysis it was identified that the achievement dimension obtained higher score, moreover, more than 90% of the participants present entrepreneurial behavioral characteristics and intend to undertake. Then, behavioral characteristics and entrepreneurial intention were related by developing a structural model for entrepreneurial behavior. It was concluded that the model is apt to measure entrepreneurial behavior. The research was limited to the construction of a model of measurement of entrepreneurial behavior from the instruments answered by undergraduate students from a public higher education institution. Future studies can expand the constructs addressed in the structural model, as well as be replicated in other institutions of higher or basic education in order to compare, deepen and new findings, in addition to considering a longitudinal follow-up. The originality of the study lies in the development of a structural model for measuring entrepreneurial behavior.